Comparison of the kinetics and magnitude of antibody responses to different SARS-CoV-2 proteins in Sinopharm/BBIBP-CorV vaccinees following the BNT162b2 booster or natural infection. - Chandima Jeewandara; Inoka Sepali Aberathna; Shashika Dayarathna; Thashmi Nimasha; Thushali Ranasinghe; Jeewantha Jayamali; Achala Kamaladasa; Maneshka Karunanada; Lahiru Perera; Graham S Ogg; Gathsaurie Neelika Malavige (PLoS ONE)
The kinetics and magnitude of antibody responses to different proteins of the SARS-CoV-2 virus in Sinopharm/BBIBP-CorV vaccinees has not been previously studied. Therefore, we investigated antibody responses to different SARS-CoV-2 proteins at 2 weeks, 3 months, and 6 months post-second dose in previously infected (n = 20) and uninfected (n = 20) Sinopharm/BBIBP-CorV vaccinees. The IgG antibodies to the S, S1 and S2 and N were several folds higher in those who had natural infection compared to uninfected individuals at all time points. We then compared the persistence of antibody responses and effect of natural omicron infection or BNT162b2 booster in Sinopharm/BBIBP-CorV vaccinees. We measured the total antibodies to the RBD, ACE2 blocking antibodies and antibody responses to different SARS-CoV-2 proteins in Sinopharm vaccinees at 7 months post second dose, including those who remained uninfected and not boosted (n = 21), or those who had previous infection and who did not obtain the booster (n = 17), those who were not infected, but who received a BNT162b2 booster (n = 30), or those who did not receive the booster but were infected with omicron (n = 29). At 7 months post second dose uninfected (no booster) had the lowest antibody levels to the RBD, while omicron infected vaccinees showed significantly higher anti-RBD antibody levels (p = 0.04) than vaccinees who received the booster. Only 3/21 cohort A (14.3%) had ACE2 blocking antibodies, while higher frequencies were observed in naturally infected individuals (100%), those who received the booster (18/21, 85.7%), and omicron infected individuals (100%). Pre-vaccination, naturally infected had the highest antibody levels to the N protein. These data suggest that those previously infected Sinopharm/BBIBP-CorV vaccinees have a robust antibody response, 7 months post vaccination, while vaccinees who were naturally infected with omicron had a similar immune response to those who received the booster. It will be important to investigate implications for subsequent clinical protection.